Relationship Between Activities Of Daily Living And Depression In Elderly - Dominica, Diva Shirleen; Solihah, Ii; Rianti, Emy (Jurnal Kesehatan Manarang, 2024)
Background. Activities of daily living are activities that are carried out routinely. Elderly who experience physical changes and decreased body function will show a lack of independence in daily activities, one of the causes of the elderly being susceptible to mental changes, namely depression. This study aims to analyze the relationship between the ability to carry out activities of daily living and depression in the elderly. Method. This research is a cross sectional research. The population of this study is the elderly who live in RW 08 Kebagusan Village with a sample of 100 people. Sampling using simple random sampling. Data analysis used the Spearman Rank test. Result. Bivariate analysis using the Spearman Rank test. Statistically, the results of basic ADL with depression in the elderly (r=0.60, p=0.000) and instrumental ADL with depression in the elderly (r=0.68, p=0.000). Conclusion. There is a significant relationship between the ability to carry out activities of daily living and depression in the elderly in RW 08 Kebagusan Village, South Jakarta City.